2023
DOI: 10.1002/anie.202301574
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization Strategies to Construct a 3D Polymer Passivation Network toward High Performance Perovskite Solar Cells

Abstract: The spontaneously formed uncoordinated Pb 2 + defects usually make the perovskite films demonstrate strong n-type with relatively lower carrier diffusion length and serious non-radiative recombination energy loss. In this work, we adopt different polymerization strategies to construct three-dimensional passivation frameworks in the perovskite layer. Thanks to the strong C�N•••Pb coordination bonding and the penetrating passivation structure, the defect state density is obviously reduced, accompanied by a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…It can be found that, the stretching vibration peak of TMBAI shifts from 1578 to 1604 cm −1 , indicating a strong interaction between TMBAI and PbI 2 . [40,41] Steady-state photoluminescence (PL) and transient photoluminescence (TRPL) measurements were used to study the optoelectronic quality of the perovskite films. PL and TRPL measurements on samples with structures FTO/TiO 2 /perovskite/with and without TMBAI layer and FTO/Al 2 O 3 / perovskite/with and without TMBAI layer, respectively, are shown in Figure 2a,b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found that, the stretching vibration peak of TMBAI shifts from 1578 to 1604 cm −1 , indicating a strong interaction between TMBAI and PbI 2 . [40,41] Steady-state photoluminescence (PL) and transient photoluminescence (TRPL) measurements were used to study the optoelectronic quality of the perovskite films. PL and TRPL measurements on samples with structures FTO/TiO 2 /perovskite/with and without TMBAI layer and FTO/Al 2 O 3 / perovskite/with and without TMBAI layer, respectively, are shown in Figure 2a,b.…”
Section: Resultsmentioning
confidence: 99%
“…It can be found that, the stretching vibration peak of TMBAI shifts from 1578 to 1604 cm −1 , indicating a strong interaction between TMBAI and PbI 2 . [ 40,41 ]…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the functional groups in cross-linker contribute to regulating the crystallization of perovskite and consequently induces the formation of high-quality perovskite. [91,93,94,98,113] Li et al [98] revealed that ether and carboxyl in the cross-linkable additive trimethylolpropane ethoxylated triacrylate (TET) can coordinate with Pb 2+ and form the hydrogen with FA + , which reduces the crystallization of perovskite and results in the increasement of average grain size of perovskite from 313 nm to 505 nm (Figure 4a,b). Since the horizontal grain boundaries in perovskite are detrimental to the carrier diffusion and extraction, larger crystal grains run through the whole perovskite film are beneficial to the photovoltaic performance of PSCs.…”
Section: Crystallization Regulationmentioning
confidence: 99%
“…[14][15][16] Meanwhile, the use of conjugated polymers can alleviate this issue, and poly[(2,6-(4,8-bis(5-(2-ethylhexyl)-thiophen-2-yl)benzo[1,2-b:4,5-b′]dithiophene)-alt-(5,5-(1′,3′-di-2-thienyl-5′,7′bis(2-ethylhexyl)benzo [1′,2′-c:4′,5′-c′]dithiophene-4,8-dione))] (PBDB-T), poly[N-9′-heptadecanyl-2,7-car-bazole-alt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole)] (PCDTBT), and poly[[N,N′bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis (dicarboximide)−2,6diyl]-alt-5,5′-(2,2′-bithiophene)] (N2200), which have charge carrier mobility and hydrophobicity, have been used for passivating GBs of perovskite films. [17][18][19][20][21][22][23][24] These polymers generally include Lewis base elements, such as O, N, and S, which form Lewis adducts with Lewis acids, such as under-coordinated Pb 2+ ions, to restore the GBs. [14,16,17,25,26] However, given the ambipolar charge transport characteristics of perovskite materials, previously reported conjugated polymers with one-sided p-type or n-type characteristics can impede opposite charge transport when incorporated into the GBs of perovskite films.…”
Section: Introductionmentioning
confidence: 99%